Is the call to reduce heading exposure in professional football to prevent dementia evidence-based? - Gouttebarge, V. (BMJ Open Sport & Exercise Medicine, 2021)
A Scottish study found in 2019 that the mortality from neurodegenerative diseases, particularly dementia, was higher in former professional footballers than in the general population.1 Dementia is a syndrome of progressive deterioration in various brain functions (eg, memory, thinking, ability to perform activities) beyond what might be expected within normal ageing.2 Several risk factors for dementia have been established, including ageing, low education, low mental activity, obesity, physical inactivity, depression and traumatic brain injury.2 Principally in the wake of the aforementioned Scottish study, professional football stakeholders, former players, charities and media have repeatedly been calling to reduce heading in professional football in order to prevent dementia. However, Is this call currently backed with sufficient and robust epidemiological evidence? This editorial reflects on several key questions that must be answered before we can provide decision-makers with concrete and safe evidence-based guidelines for professional football.